2022
DOI: 10.1002/cre2.644
|View full text |Cite
|
Sign up to set email alerts
|

A novel pilot animal model for bone augmentation using osseous shell technique for preclinical in vivo studies

Abstract: Objectives: Bone grafting is commonly used to reconstruct skeletal defects in the craniofacial region. Several bone augmentation models have been developed to evaluate bone formation using novel bone substitute materials. The aim of this study was to evaluate a surgical animal model for establishing a three-dimensional (3D) grafting environment in the animal's mandibular ramus for bone augmentation using the osseous shell technique, as in humans.Materials and Methods: Osteological survey of New Zealand white (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several previous studies, both in vivo and human clinical trials, have demonstrated that dentin-derived ABG is well-tolerated when used to fill ridge defects and to preserve post-extraction sockets; thus, this material is expected to provide clinically beneficial results following an alveolar augmentation procedure. 16 , 17 , 18 , 19 Hence, This systematic review was carried out to assess the available clinical evidence regarding the effectiveness of dentin-derived ABG in alveolar augmentation procedures, specifically focusing on post-extraction sockets and other defects in the alveolar bone. The reporting is based on the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) 2020 checklist.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies, both in vivo and human clinical trials, have demonstrated that dentin-derived ABG is well-tolerated when used to fill ridge defects and to preserve post-extraction sockets; thus, this material is expected to provide clinically beneficial results following an alveolar augmentation procedure. 16 , 17 , 18 , 19 Hence, This systematic review was carried out to assess the available clinical evidence regarding the effectiveness of dentin-derived ABG in alveolar augmentation procedures, specifically focusing on post-extraction sockets and other defects in the alveolar bone. The reporting is based on the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) 2020 checklist.…”
Section: Introductionmentioning
confidence: 99%